2013
DOI: 10.2527/jas.2013-6678
|View full text |Cite
|
Sign up to set email alerts
|

Selection of SNP from 50K and 777K arrays to predict breed of origin in cattle1

Abstract: Reliable breed assignment can be performed with SNP. Currently, high density SNP chips are available with large numbers of SNP from which the most informative SNP can be selected for breed assignment. Several methods have been published to select the most informative SNP to distinguish among breeds. In this study, we evaluated Delta, Wright's FST, and Weir and Cockerham's FST, and extended these methods by adding a rule to avoid selection of sets of SNP in high linkage disequilibrium (LD) providing the same in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 19 publications
0
44
0
Order By: Relevance
“…In fact, where there is sufficient genetic heterogeneity among populations, a few genetic markers can be easily used to identify and verify the origin of individuals, whereas it becomes more complicated for population with low genetic differentiation, such as the sheep breeds involved in this study (Mastrangelo et al, 2012;Tolone et al, 2012). It is well known that a high number of genotyped animals can capture the whole within population variability reducing the possibility that some individuals would not be assigned correctly due to atypical genotypes (Hulsegge et al, 2013). Considering the high level of admixture among these sheep breeds , and the relative low number of analysed individuals, our study reported relevant results.…”
Section: Discussionmentioning
confidence: 68%
“…In fact, where there is sufficient genetic heterogeneity among populations, a few genetic markers can be easily used to identify and verify the origin of individuals, whereas it becomes more complicated for population with low genetic differentiation, such as the sheep breeds involved in this study (Mastrangelo et al, 2012;Tolone et al, 2012). It is well known that a high number of genotyped animals can capture the whole within population variability reducing the possibility that some individuals would not be assigned correctly due to atypical genotypes (Hulsegge et al, 2013). Considering the high level of admixture among these sheep breeds , and the relative low number of analysed individuals, our study reported relevant results.…”
Section: Discussionmentioning
confidence: 68%
“…These SNPs with high LD were derived by the PCA selection procedure that selected quite a high number of SNPs in high LD (data not shown). This is a problem that has been already observed in PCA selected SNPs (Paschou et al 2007;Hulsegge et al 2013). However, RFs procedures reduced a lot the number of these SNPs (only 6 of 96 SNPs were in LD with another one of this panel), suggesting that a preselection step of the SNPs based on the value of r 2 could be superfluous.…”
Section: Random Forestsmentioning
confidence: 84%
“…Previously performed editing steps to remove uninformative SNP are described by Hulsegge et al . (). In short, Holstein Friesian animals were genotyped with a BovineSNP50 BeadChip and imputed to the BovineHD BeadChip using Beagle (Browning & Browning ).…”
Section: Methodsmentioning
confidence: 97%
“…These data included 1287 purebred cows; 989 were Holstein Friesian (HF), 97 Groningen White headed (GWH), 137 Meuse-Rhine-Yssel (MRY) and 64 Dutch Friesian (DF). Previously performed editing steps to remove uninformative SNP are described by Hulsegge et al (2013). In short, Holstein Friesian animals were genotyped with a BovineSNP50 BeadChip and imputed to the BovineHD BeadChip using Beagle (Browning & Browning 2009).…”
Section: Animals and Genotypesmentioning
confidence: 99%